Skill mix in medical and about medical professions - Iwona Kowalska-Bobko; Małgorzata Gałązka-Sobotka; Aldona Frączkiewicz-Wronka; Katarzyna Badora-Musiał; Beata Buchelt (Medycyna Pracy, 2020)
An important problem faced by many healthcare systems is the shortage of medical staff, and in particular doctors and nurses. Their number, competences and qualifications determine the level of availability and quality of medical services. Unfortunately, the demand for medical services is increasing, along with the progressive aging of the population, as well as the increase in the incidence of chronic diseases and frequent reforms of health systems. Employee costs related to healthcare are the most burdensome for the system; therefore, based on the available resources, it is necessary to create effective teams of sector employees. This results in rationalizing employment, or providing new medical and about medical competencies to new groups of professionals, which gives rise to the skill mix phenomenon. A well-prepared and implemented skill mix contributes to improving the quality of patient care, increased patient satisfaction and better clinical outcomes. In the process of mixing of competences, the roles that have been exercised so far are being changed. While some professionals are expanding their existing roles, other employees are required to accept some aspects of the previous roles. In Poland, in order to counteract such negative trends (the shortage of doctors), changes have been introduced to increase access to medical services (e.g., nurses and midwives being vested with the right to issue prescriptions and medical ordinances, paramedics – with the right to perform medical emergency services and provide healthcare services, and physiotherapists – with the right to conduct independent physiotherapeutic visits). A new profession of a medical coordinator has also been introduced. Med Pr. 2020;71(3):337–52